IN VITRO ANTIOXIDANT ACTIVITY OF ETHANOLIC EXTRACT OF TERMINALIA CATAPPA LEAVES - N, DIVYA; A, VIJAYA ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Free radicals are the important role in causing various kinds of diseases. Free radicals neutralized with the help of antioxidants, so the aim of this study is to find out the antioxidant potential of ethanolic extract of Terminalia catappa Linn. leaves by in vitro models. Methods: The plant material is collected, authenticated, dried, and grind into powder. The powdered plant material is subjected to successively Soxhlet extraction with a solvent of ethanol. Ethanol extract of leaves were taken and the extract is subjected to reducing power assay, H assay, nitric oxide assay, and 2,2-diphenylpicrylhydrazyl (DPPH) assay by using standardized methods. Results: The results of all the assays proved that the ethanolic extract of T. catappa has an antioxidant potential on a dose-dependent manner. The highest percentage of reducing power (78.04%) is recorded at 500 Î¼g/ml, 500 Âµg/ml have a (56.4%) of scavenging activity, (74.68%) activity of nitrous oxide production and DPPH percentage of inhibition is (99.6%). The results were compared with the antioxidant activity of standard ascorbic acid. Conclusion: The study proves that the ethanolic extract of T. catappa leaves is a good source of antioxidants, and future medicated world choose this phytochemical constituent rich plant for their drug preparation after the deepness of research. In all the methods the plant leaves has been found to possess the antioxidant activity. which may be the responsible for various therapeutic properties. The current study showing that T.catappa is having high quantity of phytochemicals and a worthy source of natural antioxidants. Using this kind of herbal medicine we can lead the life with harmless drug for harmful illness. Keywords: Terminalia catappa, Reducing power assay, Hydrogen peroxide assay, Nitric oxide assay and 2-2-diphenyl-1-picrylhydrazylassay.